Implantes cigomáticos como una nueva alternativa en la rehabilitación oral de maxilares atróficos. - Cáceres Guerrero, María Fernanda (2025)
The objective of this study was to analyze zygomatic implants as a new alternative for the oral rehabilitation of atrophic jaws. The methodology was performed using the PRISMA protocol, resulting in a non-experimental, cross-sectional literature review. A search was conducted in recognized databases such as Scopus, ScIELO, PubMed, and EBSCO; from the sources obtained, those that met the selection criteria were included in the study. Scientific articles, systematic and literature reviews, clinical case reports, and meta-analyses were considered, all of which were free, in Spanish and English, and published in the last 10 years. After completing the search, 23 studies were obtained, and after analyzing the information, it was determined that zygomatic implants offer multiple benefits, such as shorter treatment times, a reduced number of surgical procedures, the option of immediate loading, and high success rates. Likewise, the complications and challenges posed by this treatment were highlighted, including sinusitis, peri-implantitis, mucositis, infections, and hematomas, which have a low recurrence rate and are treatable. Additionally, these implants have demonstrated greater efficacy compared to conventional treatments, presenting much faster immediate loading, a lower failure rate, and a high level of satisfaction according to the VAS scale. Therefore, it is concluded that this is an effective and viable alternative for the rehabilitation of atrophic jaws.